Brain-derived neurotrophic factor (BDNF) expression and function in the mammalian reproductive Tract. (7th May 2020) - Chow, R; Wessels, J M; Foster, W G
Abstract: BACKGROUND: Neurotrophins of the nerve growth factor family are soluble polypeptides that are best known for their role in nerve growth, survival and differentiation in the central nervous system. A growing body of literature shows that neurotrophins and their receptors are also expressed throughout the reproductive tract. OBJECTIVE AND RATIONALE: Neurotrophins are key regulatory proteins in reproductive physiology during development and throughout adult life. Of the neurotrophins, the literature describing the expression and function of brain-derived neurotrophic factor (BDNF) and its high-affinity receptor, neurotrophin receptor kinase-2 (NTRK2), has been expanding rapidly. We therefore conducted a systematic inductive qualitative review of the literature to better define the role of the BDNF in the reproductive tract. We postulate that BDNF and NTRK2 are central regulatory proteins throughout the reproductive system. SEARCH METHODS: An electronic search of Medline (PubMed) and Web of Science for articles relating to BDNF and the reproductive system was carried out between January 2018 and February 2019. OUTCOMES: In the ovary, BDNF expression and levels have been linked with follicle organisation during ovarian development, follicle recruitment and growth and oocyte maturation. In the endometrium, BDNF is involved in cell proliferation and neurogenesis. In contrast, literature describing the role of BDNF in other reproductive tissues is sparse and BDNF-NTRK2 signalling in the male reproductive tract has been largely overlooked. Whilst estradiol appears to be the primary regulator of BDNF expression, we also identified reports describing binding sites for glucocorticoid and myocyte enhancer factor-2, a calcium-response element through activation of an N-methyl-D-aspartate (NMDA) receptor, and aryl hydrocarbon receptor nuclear transporter protein-4 (ARNT) response elements in promoter regions of the BDNF gene. Expression is also regulated by multiple microRNAs and post-translational processing of precursor proteins and intracellular shuttling. BDNF-NTRK2 signalling is modulated through tissue specific receptor expression of either the full-length or truncated NTRK2 receptor; however, the functional importance remains to be elucidated. Dysregulation of BDNF expression and circulating concentrations have been implicated in several reproductive disorders including premature ovarian failure, endometriosis, pre-eclampsia, intra-uterine growth restriction (IUGR) and several reproductive cancers. WIDER IMPLICATIONS: We conclude that BDNF and its receptors are key regulatory proteins central to gonadal development, ovarian regulation and uterine physiology, as well as embryo and placenta development. Furthermore, dysregulation of BDNF-NTRK2 in reproductive diseases suggests their potential role as candidate clinical markers of disease and potential therapeutic targets.